Is Eotaxin‐1 a serum and urinary biomarker for prostate cancer detection and recurrence?. Issue 16 (26th August 2015) - Heidegger, Isabel; Höfer, Julia; Luger, Markus; Pichler, Renate; Klocker, Helmut; Horninger, Wolfgang; Steiner, Eberhard; Jochberger, Stefan; Culig, Zoran
ABSTRACT INTRODUCTION AND OBJECTIVES Eotaxin‐1 (CCL11) is a protein expressed in various tissues influencing immunoregulatory processes by acting as selective eosinophil chemo‐attractant. In prostate cancer (PCa), the expression and functional role of CCL11 have not been intensively investigated so far. Therefore, the aim of the present study was to investigate the diagnostic or prognostic potential of Eotaxin‐1 in PCa patients. MATERIALS AND METHODS We analyzed serum from 140 patients who have undergone prostate biopsy due to elevated prostate‐specific antigen (PSA) levels as well as serum of 20 individuals with PSA levels < 1ng/ml (healthy control group). Moreover, 40 urine samples were analyzed. A custom‐made Q‐Plex array ELISA (Quansys Biosciences) for the detection of Eotaxin‐1 was performed and Q‐View Software used for quantification. In addition, clinical courses of patients documented in our Prostate Biobank database were analyzed. ROC and survival analyses were used to determine the diagnostic and prognostic power of Eotaxin‐1 levels. RESULTS Serum Eotaxin‐1 levels were significantly decreased in PCa (P = 0.006) as well as in benign prostate hyperplasia (P = 0.0006) compared to the control group. ROC analysis revealed that Eotaxin‐1 is a significant marker to distinguish PCa from disease‐free prostate. Moreover, we found that Eotaxin‐1 expression is significantly decreased in Gleason score (GS) 6 (P = 0.0135) and GS 8 (P = 0.0057) patients compared to samples of healthy men, respectively. However, PCa aggressiveness was not predictable by Eotaxin‐1 levels. In line with serum analyses, urine Eotaxin‐1 was significantly decreased in patients with PCa compared to cancer‐free individuals (P = 0.0185) but was not different between cancers of different GS. Patientś follow‐up analyses showed no significant correlation between serum Eotaxin‐1 levels and time to biochemical recurrence. Survival analyses also revealed no significant changes in progression‐free survival among low (≤ 112.2 pg/ml) and high (> 112.2 pg/ml) Eotaxin‐1 serum levels. CONCLUSION Although this study has not established a prognostic role of Eotaxin‐1 in PCa patients, this chemokine may serve as a diagnostic marker to distinguish between disease‐free prostate and cancer. Prostate 75:1904–1909, 2015. © 2015 Wiley Periodicals, Inc.